EFFECT OF PICRORHIZA KURROA ROOTS ON BLOOD GLUCOSE LEVEL ON ALLOXAN INDUCED DIABETIC RATS - Hurakadle, P.; Patil, M.; Jalalpure, S.; Manvi, F. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The polar and nonpolar solvent extracts of Picrorhiza kurroa roots were screened at the oral dose of 250 mg/kg body weight for antidiabetic activity using alloxan induced diabetic rats on prolonged treatment studies. Petroleum ether, alcoholic and aqueous extracts of roots of Picrorhiza kurroa showed significant (p<0.01) antidiabetic results with prolonged treatment studies. The extracts contained alkaloids, flavonoids and glycosides. The results were comparable with the standard drug glibenclamide and a standard marketed herbal product, which revealed that sterols in petroleum ether extract, flavonoids, alkaloids and glycosides in alcoholic and aqueous extracts were responsible for antidiabetic activity.